Cross-Sectional Associations of Neighborhood Perception, Physical Activity, and Sedentary Time in Community-Dwelling, Socioeconomically Diverse Adults - Claudel, Sophie E.; Shiroma, Eric J.; Harris, Tamara B.; Mode, Nicolle A.; Ahuja, Chaarushi; Zonderman, Alan B.; Evans, Michele K.; Powell-Wiley, Tiffany M. (Frontiers in Public Health, 2019)
Background: Little is known about the role of perceived neighborhood environment as a determinant of physical activity (PA) and sedentary time (ST) in understanding obesity-related health behaviors. We focus on a biracial, socioeconomically diverse population using objectively measured ST, which is under-represented in the literature. Methods: We examined the association between self-reported neighborhood perception (Likert-scale questions), PA using the Baecke questionnaire, and both non-sedentary time and ST using accelerometry from wave 4 of the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study (n=2167). After applying exclusion criteria, the sample size was n=1359 for analyses of self-reported PA and n=404 for analyses of accelerometry data. Factor analysis identified key neighborhood characteristics to develop a total neighborhood perception score (NPS). Higher NPS indicated less favorable neighborhood perception. Linear regression was used to determine the relationship between NPS, PA, non-sedentary time, and ST. Results: Complete data were available for n=1359 (age 56.6(9.0) years, 59.5% female, 62.2% African American) for whom we identified four neighborhood perception factors: 1) concern about crime 2) physical environment, 3) location of violent crime, and 4) social environment. Worsening perception of the overall neighborhood [β=-0.13(SE=0.03); p=0.001], the physical environment [-0.11(0.05); p=0.03], and the social environment [-0.46(0.07); p<0.0001] were associated with decreased PA. Worsening perception of the overall neighborhood [1.14(0.49); p=0.02] and neighborhood social environment [3.59(1.18); p=0.003] were associated with increased ST over the day. There were no interactions for race, sex, poverty status, or economic index. Conclusion: Poor overall neighborhood perception, perceived social environment, and perceived neighborhood physical environment are associated with PA and ST in a multi-racial, socioeconomically diverse cohort of urban adults.